Comparison and application of depression screening tools for adolescents: scale selection and clinical practice - Xinyu Li; Wei Jin; Lu Han; Xingyu Chen; Lihong Li (Child and Adolescent Psychiatry and Mental Health)
Abstract Background Clinical assessments rely primarily on patients’ emotional expressions and scale scores. However, due to cognitive differences and the complexity of emotional expression among adolescents, existing assessment tools often present challenges in their selection and application. This study reviews and analyzes the literature related to 8 commonly used adolescent depression assessment scales, including the Hamilton Depression Scale (HAMD), the Beck Depression Inventory (BDI), the Center for Epidemiologic Studies Depression Scale (CES-D), the Reynolds Adolescent Depression Scales (RADS), the Children’s Depression Inventory (CDI), the Kutcher Adolescent Depression Scale (KADS), the Patient Health Questionnaire (PHQ) and the Depression Screener for Teenagers (DesTeen). Through a comprehensive analysis of each scale’s strengths, limitations and practical applications, this narrative review aims to guide healthcare practitioners and researchers in selecting optimal measurement tools for different clinical and research contexts. Methods Relevant studies on 8 frequently used or well-supported adolescent depression assessment scales (CDI, RADS, CES-D, BDI, PHQ, KADS, HAMD, DesTeen) were retrieved from PubMed, Web of Science, CNKI, and Wanfang databases. A total of 102 articles were ultimately selected for data extraction to determine the reliability and validity of these scales. Additionally, 13 original development studies of the included scales were further reviewed to extract and analyze information on their developmental background, structural dimensions, item composition, and applicability. Results Recent studies on depression assessment scales have focused on the development of precise diagnosis and personalized evaluation. All 8 adolescent depression assessment scales generally exhibit good reliability and validity. Among them, the HAMD is used for detailed clinical evaluation of depressive symptoms but suffers from complexity due to its reliance on professional assessors. The BDI and the CES-D provide the most comprehensive dimensions. While the BDI is suitable for clinical assessments, it has the drawback of containing items that may be difficult to understand. The CES-D is well-suited for epidemiological research and large-scale screenings but has the limitation of unclear differentiation between emotional and somatic symptoms. The RADS is recognized for its comprehensive items and high reliability and validity, although its lengthy items may lead to respondent fatigue. The CDI allows multidimensional assessment of depressive symptoms but has been debated regarding its applicability across different age groups. The KADS, explicitly designed for adolescents, is a promising tool; however, its relatively recent development has resulted in limited validation studies. The PHQ is appropriate for rapid screening and tracking treatment effects but lacks sufficient emotional evaluation. The DesTeeen, designed for adolescents, features concise and clear item phrasing, but it’s only available in the German language. Conclusions The 8 standard scales demonstrate high accuracy in screening adolescent depression, but challenges persist in selecting scales for different contexts and ensuring their cross-cultural validity.